Characteristics of Mothers with Children Under Five Participating in Integrated Health Care Service Activities at Tarus Community Health Center - Longa, Teodora Selvia; Junias, Marylin Susanti; Hinga, Indriati A. Tedju (Faculty of Public Health, Nusa Cendana University, 2024)
Posyandu (Integrated Health Post) is a basic health activity organized by, from, and for the community to reduce infant mortality rates, maternal mortality rates (pregnant, childbirth, and postpartum mothers), promote small, prosperous families, and enhance community participation and capability in health and family planning activities. This study aimed to describe the characteristics of mothers of children under five who participated in posyandu activities in the working area of Tarus Health Center in 2022. The study used a descriptive method with a cross-sectional design, involving 97 mothers of children aged 0–60 months selected through purposive sampling from a population of 3,675 registered at posyandu. The results showed that 52.5% of respondents actively visited posyandu, while 47.4% were inactive. Most mothers were aged 21–25 years (36.1%), had a high school education (41.2%), and were housewives (51.5%). Additionally, 59.8% of mothers had good knowledge about posyandu, and 54.6% lived close to posyandu. The study suggests that the health center enhances understanding and awareness among mothers to routinely attend posyandu every month to monitor the growth and development of their children.